Women's economic empowerment and protection social rights in preventing domestic violence - Ahmad, Nadzrah; Mohd Yusoff, Rahmawati; Quddus, Abdul (Centre for Environment-Behaviour Studies, Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia., 2022)
Gender equality in terms of economic participation and social standing of women appears to have contributed to violations of women's rights. Compared to their peers with higher social positions, women with poor financial and social status are more likely to be victims of domestic violence and abuse. As a result, women's economic empowerment became critical to ensuring equal social treatment. Inequality in gender treatment can lead to abuse, harassment, and violence in the future. Female labor force participation in Malaysia is low compared to male labor force participation. Perhaps because women in Malaysia are economically under-empowered and have a social standing equivalent to men, they are more vulnerable to abuse. Hence, this paper aims to examine the economic empowerment of women in Malaysia and preserve their social rights in the face of domestic violence. This study aims to examine the current framework for women's economic empowerment and the protection of their social rights against domestic violence, as well as the challenges of implementing it, and to propose a framework for women's economic empowerment and the protection of their social rights against domestic violence as part of Malaysian government inclusive development. The analysis is based on a qualitative and descriptive cross-sectional analysis of the governing statutes, reported cases, and data gathered from the respective administrative authorities. The research found that prejudice and oppression against women are not sufficiently addressed in Malaysia due to low economic participation and insufficient observance of social rights. Women in Malaysia are still susceptible to various forms of violence perpetrated by their spouses, despite international concern about violence as a crime against humanity. Therefore, the research seeks to produce a new model of women's inclusive development that promotes greater economic participation and protects their social rights from domestic violence. The findings of this study are expected to serve as a guide for the Government in addressing national concerns about gender equality and gender-based violence, particularly against women.